KESIAPAN FISIK DALAM KEBERHASILAN TOILET TRAINING PADA BALITA - Buston, Erni (JURNAL MEDIA KESEHATAN, 2017)
Development theory states that toddler children enter the anal stagecharacterized by the development of satisfaction (kateksis) and dissatisfaction(antikateksis) around the elimination function. Failure of toilet training can be caused dueto the use of diapers up to the age of 4 years so as to increase the risk of bladderproblems. This study uses a quantitative research with descriptive design with crosssectional analytic. The sample in this study is the mother and child in early childhoodeducation and early childhood Baitul Izzah Ababil Bengkulu city bumbering 81 people.The collection of data by using a questionnaire sheet. The data analysis was conductedquantitative univariate and bivariat using Chi Square.The result of this study, the norelation between eduction and the mother with the success of implementing toilet trainingin childern in early childhood Ababil Izzah Bengkulu City 2016 p:0,663), there is arealitionship attitude to the success of implementing Toilet training on their childern inearly childhood Ababil and Baitul Izzah Bengkulu city 2016 (p:0,016) no relitionshipPhysical Readiness to implement successful Toilet Traning in Childern in early childhoodeducarion and Baitul Izzah Bengkulu city in 2016 (p:0,001).Expected early childhoodteaching team can implement Toilet Taning activities on childern in eraly childhoodeducation dropped off to improve gross motor development of childern so tahat childernstill do development.